Combined effects of helical force and rotation on stationary convection of a binary ferrofluid in a porous medium - Kpossa, Gbedodé Mathieu; Monwanou, Vincent A. (Zielona Góra: Uniwersytet Zielonogórski)
This work studies the simultaneous e?ects of helical force, rotation and porosity on the appearance of stationary convection in a binary mixture of a ferro?uid and on the size of convection cells. We have determined the analytical expression of the Rayleigh number of the system as a function of the dimensionless parameters.
Keywords: helical force; stationary convection; binary mixture of ferro?uid; porous medium; rotation